2014
DOI: 10.3390/plants3040583
|View full text |Cite
|
Sign up to set email alerts
|

Plasmolysis: Loss of Turgor and Beyond

Abstract: Plasmolysis is a typical response of plant cells exposed to hyperosmotic stress. The loss of turgor causes the violent detachment of the living protoplast from the cell wall. The plasmolytic process is mainly driven by the vacuole. Plasmolysis is reversible (deplasmolysis) and characteristic to living plant cells. Obviously, dramatic structural changes are required to fulfill a plasmolytic cycle. In the present paper, the fate of cortical microtubules and actin microfilaments is documented throughout a plasmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 43 publications
1
34
0
2
Order By: Relevance
“…The loss of water is accompanied by shrinkage of the bulk tissue 13 and changes in microstructure, including cell collapse, cell shrinkage, cell membrane detachment (plasmolysis) or cell membrane breakage (lysis). [14][15][16] These changes strongly inuence the moisture transport properties of the tissue 17 and also induce variations in the nal product quality. The product texture is inuenced for example by the bulk density, porosity, cell size, cell shape and cell wall thickness of the dried product.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of water is accompanied by shrinkage of the bulk tissue 13 and changes in microstructure, including cell collapse, cell shrinkage, cell membrane detachment (plasmolysis) or cell membrane breakage (lysis). [14][15][16] These changes strongly inuence the moisture transport properties of the tissue 17 and also induce variations in the nal product quality. The product texture is inuenced for example by the bulk density, porosity, cell size, cell shape and cell wall thickness of the dried product.…”
Section: Introductionmentioning
confidence: 99%
“…Water loss beyond the zero turgor point induces several responses depending on the initial shape and size of the cell, the viscosity of the protoplast and the environmental conditions (Oparka 1994). There are three typical dehydration responses of a fruit cell after losing its turgor pressure (condition III in Figure 2) (Seguí et al 2010;Lang et al 2014). The first response is free shrinkage (condition IIIa in Figure 2), which means that the cell and protoplast can continue to shrink in an unrestricted way.…”
Section: Introductionmentioning
confidence: 99%
“…Komis et al (2002) thought that actin bundles mitigate the physical stresses caused by the deformation of the plasma membrane. Wojtaszek et al (2007) and Lang et al (2014) compared these bundle structures to the stress fibres found in animal cells; they, and Komis et al (2002), suggest that the bundles are involved in maintaining the shape and regulating volume of the protoplast during plasmolysis. The mechanical properties of these 'stress fibre-like' actin bundles will be dependent on the proteins that cross-link the filaments: how tightly they bind them together and how much sliding can occur (Blanchoin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lang et al (2014) monitored the actin cytoskeleton during the onset of plasmolysis and reported that actin filaments reorganise rapidly and when the cell was fully plasmolysed they observed many actin bundles. This suggests that as the protoplasm separates from the cell wall the actin cytoskeleton rapidly alters in structure, forming bundles that become stable as the cell becomes fully plasmolysed.…”
Section: Discussionmentioning
confidence: 99%